Vertical farming of orchids - Nair, Sujatha A; Chandana, S; Smitha, G R; Kumaran, G Senthil (Indian Horticulture, 2023)
Vertical farming is fast becoming a popular option available to the growers to economize on the use of arable land and to realise higher yield and income per unit area. Use of this technology can result in a change in the conventional crop production technologies. Fine tuning the existing production practices for successful cultivation on the vertigrow system needs research on aspects like the growing media, nutrition, planting density, planting system, dispensing plant protection chemicals and other intercultural operations. Orchids are one of the high value cut flowers that are imported into India to meet the domestic demand. Cultivation of orchids on vertigrow systems with suitable agro-techniques has the potential to enhance the production of cut flowers per unit area, thereby meet the domestic demand and enhance the income of the growers.